Woodward H. Brown letter to Nicholas S. Halmi regarding bird sightings, February 7, 1978 - Brown, Woodward H.et al (1978)
Letter from Woodward H. Brown to Nicholas S. Halmi regarding bird sightings, February 7, 1978. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter, 1977-1978. Epson - sheet feed/flatbed